Climate change issues: challenges for Natural Resource Management in Bangladesh – a way forward. (18th June 2012) - Ahmed, Ferdous; Al-Amin, Abul Quasem; Alam, Gazi Mahabubul
This study aimed to understand the climate change issues in Bangladesh by focusing on the specific operational guidance to Natural Resource Management (NRM) over time. The specific justification is used to figure out the factors that are responsible. To have an effective plan and guideline, this study has emphasised on some direct required actions and alternative options for long-run measures. Moreover, this study discussed the national lacking, limitation, required action and possible course of alternative option and a way forward to overcome the problems by the subject to current research effort and value. Finally, following on the raised issues, this study has introduced enhanced framework of strategies and guidelines to the concerned body and policy-makers in Bangladesh.